Reduced power expenditure in the minimum latency transmission scheduling problem - Charalambous, Themistoklis; Klerides, Evelina; Christodoulides, Paul; Deliparaschos, Kyriakos M. (My University, 2014)
In large networks due to the large number of transmissions it is unlikely that a slot will be used only by a single wireless node. In this paper, a Cutting Plane approach is proposed in order to combine the minimum latency transmission scheduling problem with power expenditure minimization. The problem is partitioned into a Master Problem and a Subproblem; the main objective of the Subproblem is to minimize the total power expenditure. The Cutting Plane algorithm used is evaluated with regard to its performance and the outcome is that the power expenditure is reduced significantly, while achieving the minimum latency transmission scheduling. One of the drawbacks of the proposed approach, however, is the fact that although it reduces the power significantly, the computational time required is quite large, pointing to further research towards that direction.
Keywords: Minimum latency; Power control; SINR; Transmission scheduling